Thermo-mechanical properties of a regolith simulant of the mars insight mission site (2023)
The NASA Mars InSight mission is a Discovery mission aiming at to investigating the interior of the red planet to support the understanding of its formation process and that of other rocky planets. One of the many study fronts faced by the InSight Mission Science Team is the study of the properties of the material in direct contact with the lander and its instruments, some of which were deployed on the surface of the planet by using a robotic arm. This endeavour is the key objective of the Near Surface Working Group (NSWG), and the main goal of the different works and results presented in this document is related to this research goal. The lander uses three main instruments: the first one is the Seismic Experiment for Interior Structure (SEIS), a highly accurate seismometer resulting from decades of work by French institutions including Centre National des Études Spatiales CNES and Institut de Physique du Globe de Paris IPGP; this instrument is the most relevant for this work. The second one is the Heat and Physical Properties Package (HP3), a thermal probe designed to drill inside the Martian surface to depths of up to 5m. The last one is the Rotation and Interior Structure Experiment or RISE antenna, which studies the interior structure of the planet aided by the rotation movement of Mars, tracking the position of the lander and the shifting of the planets north pole to propose models of its moment of inertia. This work is aimed at characterising the surface regolith properties at the site of the Mars InSight lander, landed on Elysium Planitia since November 2018. This comprises experimental investigations on a Martian Regolith Simulant together with some complementary activities. The key questions addressed were the interaction of the SEIS with the Martian regolith in direct contact with its three feet, its very small strain stiffness (in the elastic range), as well as the thermal conductivity and the mechanical effect of atmospheric pressure fluctuations. The experimental work conducted concerns the poorly explored field of soil mechanics under very low stresses and strains (down to 1.75 kPa). Sample preparation is another question explored, since the loosest possible densities of the regolith analogue are utilised to mimic the Martian regolith. The thesis was developed within a joint supervision between the Universidad de los Andes (Bogota, Colombia) and the École des Ponts ParisTech (France). Experimental work was conducted at the facilities of both institutions. Collaborations with PhD student Maria Juliana Chaparro (Los Andes) also helped assess the dynamic properties of the regolith simulant.